Comparison of Thrombocyte Count Between Pediatric Patients With Migraine or Tension-Type Headache: A Retrospective Cohort Study. (November 2019) - Benedick, Aviv; Zeharia, Avraham; Markus, Tal Eidlitz
Hypercoagulability may explain the increased risk of thromboembolic cerebrovascular events in patients with migraine. Thrombocytes play a crucial part in the coagulation process, and some studies have demonstrated hyperaggregation of thrombocytes in adult migraineurs. We aimed to compare thrombocyte count between pediatric patients with migraine or tension-type headache and to evaluate the correlation of thrombocyte count with headache parameters. The electronic database of a tertiary pediatric headache clinic was retrospectively searched for all children and adolescents diagnosed with migraine or tension-type headache in 2016-2018. Data on thrombocyte counts were collected from the medical files and compared between the groups by parametric and nonparametric statistical tests. The cohort included 299 patients, 176 girls (59.0%) and 123 (412.0%) boys, of mean age 12.2 ± 3.4 years; 198 had migraine and 101 had tension-type headache. Among the laboratory parameters evaluated, a significantly lower mean thrombocyte number was found in the migraine group than in the tension-type headache group (282 ± 60 vs 304±71 ×10 3 /μL, P = .004). Within the migraine group, there was a significant negative correlation between the thrombocyte count and the duration of headache attacks in hours ( P < .05). No significant between- or within-group differences were found in other laboratory parameters. The low relative thrombocyte count in pediatric headache clinic patients with migraine and its negative correlation with duration of migraine suggest that migraine may be associated with a different underlying pathogenesis from tension-type headache.